A SEVENTY-FIVE YEAR WAY FROM A COLLEGE TO A UNIVERSITY - Lyudmila V. Boldyreva (Moscow Polytechnic University, 2016)
The article is devoted to the seventy fifth anniversary of the MedicalHPharmacy College, that became a separate structure of Kursk State Medical University. A special attention is paid to administrative structure and to the educational and upHbringing activities of the college.